Evaluation of land use impact on river water quality using macroinvertebrates as bioindicator in Lahumoko Watershed, Buton Island, Indonesia - KAHIRUN KAHIRUN; LAODE SABARUDDIN; MUKHTAR MUKHTAR; LAODE MUHAMMAD HARJONI KILOWASID (Society for Indonesian Biodiversity, 2019)
Abstract. Kahirun, Sabaruddin L, Mukhtar, Kilowasid LOMH. 2019. Evaluation of land use impact on river water quality using macroinvertebrates as bioindicator in Lahumoko Watershed, Buton Island, Indonesia. Biodiversitas 20: 1658-1670. The Lahumoko Watershed, a small watershed, that empties into the sea is sensitive to water quality changes due to land use changes by humans. Uncontrolled land use changes can threaten the sustainability of the river ecological functions of the watershed. It is important to examine the comparison of river water quality in locations that represent land uses. So, the objectives of this study were to reveal the impact of land use on biological water quality in rivers and to analyze the relationship between macroinvertebrates communities with parameters of biodiversity and physicochemical at the observation locations that represented land use. Biological samplings were done using a hand net with a hole size of 0.5 mm mesh, at five stations, each with three replications, with a length of 30 m of each replication, 60 minutes per station. The results of the study showed that individual abundance, family biotic index and diversity index parameters indicated that the water quality was quite good in the upstream watershed (LM1, LM2, and LM3 stations) and somewhat worse in the middle (LM4 station) and downstream of the watershed (LM5 station). The Spearman's correlation, Dendrogram, and Canonical Correspondent Analysis (CCA) showed that there were similarities among LM1, LM2 and LM3 stations, and also between LM4 and LM5 stations. Physicochemical parameters, especially the velocity and flow rate of the river flow had significant correlation with individual richness and density.